PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI DEPARTEMEN MAJOR ASSEMBLY AIRBUS HELICOPTERS MK II PT DIRGANTARA INDONESIA (PERSERO) BANDUNG - Desy Ana Rifannisa , Syarifuddin (LPPM UNIBI, 2018)
This study aims to determine the influence of organizational culture on employees performance in the Department of Major Assembly Airbus Helicopters MK II PT Dirgantara Indonesia (Persero) Bandung. Using quantitative research method and descriptive type of causality, through sampling 60 employees. Sampling technique in this research is saturated sampling that is 60 employees of Department Major Assembly Airbus Helicopters MK II PT Dirgantara Indonesia (Persero). It is known that, organizational culture has a significant effect on employee performance. Then it is also known that the magnitude of the influence of organizational culture on employee performance in the Department of Major Assembly Airbus Helicopters MK II PT Dirgantara Indonesia (Persero) is 19.5% and the remaining 80.5% influenced by other variables not examined in this study such as leadership style, work motivation, work environment, remuneration and others. The conclusion of this study is that organizational culture in Major Assembly Department of Airbus Helicopters MK II PT Dirgantara Indonesia (Persero) is very good category, but there are some items that need to be improved as the company appreciates the hard work of employees and rewards the employee's goals. Keywords : Organizational Culture, Employees Performance, Department Major Assembly Airbus Helicopters MK II PT Dirgantara Indonesia (Persero) Bandung.